UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DENGAN MODEL PROBLEM BASED LEARNING PADA SISWA KELAS V SD. - Rachel Prisilia Br. Purba; Putri Alemina br Tarigan; Gladys Nouralita Manurung; Lydia Fatricia Rumahorbo; Nova Florentina Ambarwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve students' learning outcomes in the Natural and Social Sciences (IPAS) subject on the topic "My Beloved Earth" with the subtopic Natural Disasters and Their Mitigation through the implementation of the Problem Based Learning (PBL) model. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages. The study was conducted in two cycles involving 34 fifth-grade students of SD Swasta Kartika 1-1 Medan. Data were collected through observation, tests, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques by calculating the mean scores, classical learning mastery percentages, and observation results of teacher and student activities. The findings indicated that the implementation of the Problem Based Learning model successfully improved students' learning outcomes. Classical learning mastery increased from 58.82% in the pretest to 67.65% in Cycle I and further increased to 94.12% in Cycle II. The average score also improved from 75.70 in the pretest to 81.44 in Cycle I and 93.67 in Cycle II. Furthermore, teacher activity improved from 56% to 88%, while student activity increased from 60% to 86%. Therefore, the Problem Based Learning model proved to be effective in improving students' learning outcomes while creating a more active, collaborative, and meaningful learning process in elementary school IPAS learning.